2017
DOI: 10.1016/j.colsurfb.2017.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature, water content and free fatty acid on reverse micelle formation of phospholipids in vegetable oil

Abstract: PDF/A is an ISO-standardized version of the Portable Document Format (PDF) specialized for the digital preservation of electronic documents. The extension in the file name is pdf. PDF/A differs from "normal" PDF in that features ill-suited for long-term archiving are omitted. PDF/A embeds all fonts used in the document within the PDF file, so that the user of your file will not have to have the same fonts that you used to create the file installed on their computer in order to read it. Recommended versions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 58 publications
(83 reference statements)
5
48
0
1
Order By: Relevance
“…dye solubilization or labels, can influence the association propensity by acting as nucleation sites or by otherwise disrupting the association 14,17,18 or molecular conformations 19 . Third, the presence of residual water and variations in water content in experiments make comparisons between different systems difficult as many reverse micellar systems exhibit considerable sensitivity to water 11,20,21 . Finally, impurities in especially nonionic surfactants can influence the system behaviour via introducing additional surface active components into the system 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…dye solubilization or labels, can influence the association propensity by acting as nucleation sites or by otherwise disrupting the association 14,17,18 or molecular conformations 19 . Third, the presence of residual water and variations in water content in experiments make comparisons between different systems difficult as many reverse micellar systems exhibit considerable sensitivity to water 11,20,21 . Finally, impurities in especially nonionic surfactants can influence the system behaviour via introducing additional surface active components into the system 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, the self-assembly of monoglycerides in nonpolar media has been studied extensively 15,22,[25][26][27][28][29][30][31][32] in various hydrocarbon and triglyceride solvents but only a few works address aggregate formation of diglycerides and fatty acids 21,[33][34][35] . Vapor pressure osmometry, calorimetry, light scattering, and small angle X-ray scattering (SAXS) studies indicate that small to medium sized reverse micelles of monoglycerides form in a wide range of hydrocarbon solvents 15,22,[25][26][27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…An additional factor to consider is the FFA effect on the PtdCho solubility and, subsequently, at the MGC. Within this context, Lehtinen et al () showed that oleic acid intentionally added to rapeseed oil assembled around the polar head group of lecithin molecules. The overall result was an increase in the lecithin solubility in the rapeseed oil and, subsequently, in the critical micelle concentration (Lehtinen et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, we considered that the FFA effect on PtdCho solubility was not present in our systems. Experiments currently underway in our laboratory using lower FA concentration than the one used by Lehtinen et al () are addressing the FA effect on PtdCho solubility.…”
Section: Resultsmentioning
confidence: 99%
“…La eficiencia de este proceso está muy influenciada por el contenido de gomas (fosfolípidos) en el jabón que produce un alto grado de emulsificación. Para contenidos altos de fosfolípidos solo la centrifugación es el método eficaz (Laoretani, 2017) (Lehtinen, 2017).…”
Section: Revista Especializada En Tecnología E Ingenieríaunclassified